The Association between Female Genital Cutting and Spousal HCV Infection in Egypt - Chris R. Kenyon; Robert Colebunders (International Journal of Hepatology)
Objective. To identify the risk factors for HCV infection within married couples in Egypt. Methods. In 2008 Egypt conducted its first nationally representative survey of HCV prevalence. 11126 of the 12780 individuals aged 15–59 year who were sampled agreed to participate and provided information via a questionnaire about demographic and behavioural characteristics and blood for HCV antibody and RNA analysis. We assessed the risk factors for HCV infection in a subsample of 5182 married individuals via multivariate logistic regression. Results. Overall HCV antibody prevalence in the married couples was 18.2% (95% CI, 16.8–19.6). HCV antibody prevalence was higher in the husbands (23.7%) than the wives (12.1%; P<0.001). Having a spouse who was infected with HCV was an independent risk factor for HCV infection with odds ratios of 2.1 (95% CI, 1.6–2.9) and 2.2 (95% CI, 1.6–3.1) for women and men, respectively. Husbands whose wives had experienced female genital cutting (FGC) had a higher prevalence of HCV and this relationship was driven by a strong association in urban areas. Amongst the women there was no association between FGC and HCV overall but in urban areas only women who had experienced FGC were HCV infected. Conclusions. This study provides additional evidence of the importance of intrafamilial transmission of HCV in Egypt.